Dynamic flows of polyethylene terephthalate (PET) plastic in China. (1st April 2021) - Chu, Jianwen; Cai, Yanpeng; Li, Chunhui; Wang, Xuan; Liu, Qiang; He, Mengchang
Graphical abstract: Highlights: A comprehensive model for quantifying PET flows is developed. The disposal methods of waste PET changed from 2000 to 2018. Fibers and bottles manufacturing industries are the largest PET in-use stocks. The treatment of waste PET would be a challenge in the future. Abstract: Polyethylene terephthalate (PET) is a widely used plastic material that may cause significant environmental pollution. China is a major global producer and consumer of PET. Previous studies have focused on the effects of toxic elements from PET (e.g., antimony leached from PET products) on the environment. However, detailed information about PET, particularly about the PET production, trade, use, and recycling in China, is limited. This study developed a network model of PET flows in China, including the production, market trade, manufacturing and use, and waste management and recycling stages. Based on this network model, the characteristics of PET flows during three periods of development for the PET industry were analyzed. The results show that the fiber and bottle manufacturing industries are the industries with the largest PET in-use stocks. The PET flows showed different characteristics in the terms of waste import, recycling, and disposal (mechanical recycling, chemical recycling, incineration, landfill, and discarding) in the different periods of PET industrial development. Notably, the amount of discarded PET was significant, and the treatment of waste PET would probably be a challenge in the future. Policies for improving the PET cycling system were provided on the basis of the study results to promote the management and sustainable utilization of PET materials.